Use of Monopolar Cauterization for Ectopic Intramural Ureter Correction by Cystoscopy in Bitch - Ferreira, Ariele Aparecida; Guariza Tortato, Neíse Nathalie; Teixeira, William Timboni; Peres Albernaz, Vinicius Gonzales; Carareto, Roberto; Froes, Tilde Rodrigues; Costa Castro, Jorge Luiz; Dornbusch, Peterson Trisches (Acta Scientiae Veterinariae, 2019)
Background: The ectopic ureter (EU) is considered a congenital anomaly in which the ureteral aperture opens in a position other than the bladder neck. The diagnosis involves the use of different methods or combination of image exams, including excretory urography, pneumocystography, ultrasonography, cystoscopy and computed tomography. The technics for surgical repair should be considered evaluating the number and functionality of the EU, the location of the ureteral opening, functional condition of ipsilateral kidney and the presence of other abnormalities. The case reports aims to show the surgical repair of an intramural EU in an English Bulldog bitch by cystoscopy-guides monopolar cautery. Case: A 1-year-old English Bulldog bitch received medical care due to a history of urinary incontinence since a few months of life. The animal had laboratory abnormalities compatible with lower urinary tract infection, followed by a profound growth of Klebsiella sp in urine culture, and received antibiotic treatment for 21 days based on antibiogram results. Due to a suspect EU, a urinary tract tomography was performed and indicated a congenital kidney malformation (renal dysplasia), enlargement and distal insertion of the left ureter (in comparison with the contralateral one), rising suspiciously of its intramural progression. We choose to proceed to cystoscopy examination, in which both right and left ureteral ostium could be seen in the urethral region. A guide of a pigtail catheter was inserted through both ureteral ostia in order to orient the ureteral incision. The monopolar cautery was inserted in cystoscopy working channel to section the mucosa of EU channel on urethra region, separating the lumen of EU from the urethra and extending the incision cranially inside the urinary bladder lumen. After a complete section of the ectopic tissue, a pigtail urinary catheter was correctly placed in both ureters. After bilateral repair of EU, the bitch showed a significative decrease of urinary incontinence, although completer resolution could not be obtained. Discussion:Studies showing the treatment of EU using the ablation of the tissue separating the ureteral and urethral or bladder lumen using cystoscopy-guided laser showed lower post-operative pain and hospitalization time, besides being a minimally invasive technique in comparison with traditional surgery. The limiting factor is the specialized equipment required for the procedure. In our surgical routine, there is a cystoscope, however, we do not own a diode laser or radiofrequency equipment. The adaptation of a monopolar cautery with the objective of correct an intramural EU proved to be feasible in practice since we achieved satisfactory recovery of the patient, similar than what is seen with lasers. Even after surgical repair of both EU, the patient sustained urinary incontinence, although lesser than before surgery. The remaining of the clinical sign, in this case, is compatible with the low rate of postoperative urinary continence in bitches, irrespective of the surgical technique, varying between 25% and 58% with or without medical treatment. To our knowledge, there was no published report on the use of monopolar cautery to treat EU. The monopolar cautery can be used as a less invasive and alternative technique to traditional surgery in the treatment of intramural EU through cystoscopy in bitches.